2018
DOI: 10.3389/fendo.2018.00628
|View full text |Cite
|
Sign up to set email alerts
|

Neuropeptidergic Systems in Pluteus Larvae of the Sea Urchin Strongylocentrotus purpuratus: Neurochemical Complexity in a “Simple” Nervous System

Abstract: The nervous system of the free-living planktonic larvae of sea urchins is relatively “simple,” but sufficiently complex to enable sensing of the environment and control of swimming and feeding behaviors. At the pluteus stage of development, the nervous system comprises a central ganglion of serotonergic neurons located in the apical organ and sensory and motor neurons associated with the ciliary band and the gut. Neuropeptides are key mediators of neuronal signaling in nervous systems but currently little is k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 30 publications
(43 citation statements)
references
References 58 publications
(114 reference statements)
1
42
0
Order By: Relevance
“…Further investigation of the physiological roles of luqin-type neuropeptide signaling in echinoderms could also be extended beyond adult animals to the free-swimming larval stage of these animals. Detailed anatomical analyses of neuropeptide precursor gene expression in larvae of A. rubens and S. purpuratus have been reported recently (Mayorova et al, 2016;Wood et al, 2018) but these studies did not incorporate analysis of the expression of luqin-type precursors. Therefore, this is also an important objective for future work on luqin-type neuropeptide signaling in echinoderms.…”
Section: Discovery Of Luqin-type Signaling In Ambulacrarian Deuterostmentioning
confidence: 99%
“…Further investigation of the physiological roles of luqin-type neuropeptide signaling in echinoderms could also be extended beyond adult animals to the free-swimming larval stage of these animals. Detailed anatomical analyses of neuropeptide precursor gene expression in larvae of A. rubens and S. purpuratus have been reported recently (Mayorova et al, 2016;Wood et al, 2018) but these studies did not incorporate analysis of the expression of luqin-type precursors. Therefore, this is also an important objective for future work on luqin-type neuropeptide signaling in echinoderms.…”
Section: Discovery Of Luqin-type Signaling In Ambulacrarian Deuterostmentioning
confidence: 99%
“…Moreover, the distribution of the serotonergic system in lancelet has also been studied indirectly through the expression pattern of its biosynthesis enzymes: tryptophan hydroxylase (TpH, the limiting enzyme in serotonin synthesis) and a serotonin transporter (SERT), confirming previous immunohistochemical analyses (Candiani et al, 2012). A recent work also highlighted that the development of lancelet serotonergic cells is controlled by the retinoic acid Welsh and Loveland, 1968;Nilsson et al, 1988;De Bernardi et al, 2006;Pennati et al, 2007a;Razy-Krajka et al, 2012;Braun and Stach, 2016 Phallusia mammillata Sensory vesicle, papillae, epidermal neurons Pennati et al, 2001Pennati et al, , 2003Zega et al, 2005 Styela Yaguchi et al, 2000Yaguchi et al, , 2011Yaguchi et al, , 2014Yaguchi and Katow, 2003;Katow et al, 2004, Katow et al, 2007Katow, 2008;Yao et al, 2010 Strongylocentrotus purpuratus Anterior neuroectoderm; apical organ •• Bisgrove and Burke, 1986;Burke et al, 2006Burke et al, , 2014Yaguchi et al, 2006Yaguchi et al, , 2010Materna and Cameron, 2008;Wei et al, 2009Wei et al, , 2016Squires et al, 2010;Range et al, 2013;Garner et al, 2016;Anishchenko et al, 2018;Perillo et al, 2018;Wood et al, 2018 Paracentrotus Burke et al, 2006;Leguia and Wessel, 2006;Sutherby et al, 2012...…”
Section: Cephalochordatesmentioning
confidence: 57%
“…In all echinoderms studied (with most research performed in S. purpuratus) both serotonin and tryptophan hydroxylase (the rate limiting enzyme of serotonin synthesis) are expressed specifically (i) in a population of bilaterally symmetric patches of cells in the anterior ectoderm during the early stages and (ii) in neuronal clusters in the apical organ, ciliary band and lip ganglion neurons during late larval stages (Bisgrove and Raff, 1989;Brown and Shaver, 1989;Moss et al, 1994;Chee and Byrne, 1999;Hay-Schmidt, 2000;Yaguchi et al, 2000Yaguchi et al, , 2006Yaguchi et al, , 2008Yaguchi et al, , 2010Yaguchi et al, , 2011Yaguchi et al, , 2014Yamamoto and Vernier, 2011;Beer et al, 2001;Yaguchi and Katow, 2003;Burke et al, 2006Burke et al, , 2014Nakano et al, 2006;Bishop and Burke, 2007;Byrne et al, 2007;Katow et al, 2007;Katow, 2008;Materna and Cameron, 2008;Dupont et al, 2009;Wei et al, 2009Wei et al, , 2016Yao et al, 2010;Bishop et al, 2013;Range et al, 2013;Garner et al, 2016;Jarvela et al, 2016;Anishchenko et al, 2018;Perillo et al, 2018;Wood et al, 2018).…”
Section: Echinodermsmentioning
confidence: 99%
“…Previous studies have identified sub-populations of neurons that express genes encoding different neuropeptide precursors in sea urchin larvae (Wood et al 2018). To further characterize neuronal cell types in the ciliary band nervous system of A. rubens , we used antibodies raised against the RNA-binding protein ELAV (Garner et al 2016), considered a specific neuronal marker, a sea urchin AN-peptide-type neuropeptide (Perillo et al 2018) and the A. rubens SLFMaide neuropeptide (S2).…”
Section: Resultsmentioning
confidence: 99%